2020
DOI: 10.3390/met11010049
|View full text |Cite
|
Sign up to set email alerts
|

Wear and Fretting Behavior of Cold Sprayed IN625 Superalloy

Abstract: The wear and fretting behaviour of IN625 cold spray coatings was analysed and the results are presented. The cold spray conditions were selected in order to obtain coatings with minimum porosity and maximum particles splat. This leads to compact and hard deposited material able to resist wear damaging and to dissipate energy during fretting. The coating’s strength was evaluated through nanoindentation that revealed an increased hardness from the surface toward the substrate. This different hardening behaviour … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 34 publications
0
8
0
Order By: Relevance
“…Very few experimental evidences are presented on the scratch response of cold spray deposits [39,40]. Here, nanoindentation and scratch are employed to continuously characterize the coatings mechanical properties along the deposition path.…”
Section: Introductionmentioning
confidence: 99%
“…Very few experimental evidences are presented on the scratch response of cold spray deposits [39,40]. Here, nanoindentation and scratch are employed to continuously characterize the coatings mechanical properties along the deposition path.…”
Section: Introductionmentioning
confidence: 99%
“…Delving more into the tribological responses of CS Ni-based super alloy deposits, Cavaliere et al [ 116 ] also identified the fretting-based mechanisms of CS IN625 deposit. In contrast to traditional sliding wear, fretting is another area of tribology, which focuses on the effects of low-amplitude tangential cyclic stresses along the surface.…”
Section: Tribological Propertiesmentioning
confidence: 99%
“… The ( a ) fretting wear; ( b ) COF; and OM of the wear tracks of CS IN625 deposit under ( c ) 50 N, ( d ) 100 N, and ( e ) 150 N loadings. Reprinted from Cavaliere et al, Copyright 2021 [ 116 ], under CC BY 4.0. …”
Section: Figurementioning
confidence: 99%
“…Without etching, it is evident that the number of micro pores drastically decreases as a function of process gas temperature with the lowest recorded porosity at 0.16%. Given the explanation of the increased thermal softening of the powders particles during CS process, the gradual densification of the coating suggests that there will be an improvement in particle cohesion, which can imply a greater wear resistance as porosity defects can result in early crack propagation during sliding [86,87]. Figure 8 depicts the XRD patterns of the as-sprayed coatings on Al6061 alloy substrate.…”
Section: Microstructure Of the Coatingsmentioning
confidence: 99%
“…Their intensities gradually become sharper as the loads increase, insinuating a dominant abrasive wear mechanism. Considering that S1 had a greater amount of pores, the stress concentration at the point of tribological contact which can induce fatigue cracks from the influence of circular stress due to the brittle nature of CS coatings [31,86,112]. This increases the chance of enabling a fatigue wear mechanism of which brittle fractures occur from the buildup of microslips along the contacting asperities.…”
Section: Wear Of the Bare And Coated Al6061 Alloysmentioning
confidence: 99%